Analisis Empiris Pengaruh Efektifitas Komite Audit, Efektifitas Internal Audit, Whistleblowing System, Pengungkapan Kecurangan dan Reaksi Pasar - Nur Cahyo, Mohe; Sulhani, Sulhani (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
This study was conducted to obtain answer for four research questions: (1) whether the effecivenes of audit committee affected whistleblowing system, (2) whether the effectivenes of internal audit affected whistleblowing system, (3) whether whistleblowing system affected fraud disclosure, and (4) whether fraud disclosure affected market reaction. This research was analyzed using Structural Equation Modeling SEM with PLS model. The samples were 57 companies that listed on the IDX in year 2014. Results of the study were summarized as follow: (1) The effectivenes of audit committee had negative significant effect on whistleblowing system, (2) The effectiveness of internal audit did not have effect on whistleblowing system, (3) whistleblowing system did not have effect on fraud disclosure, and (4) fraud disclosure had negative significant effect on stock market reaction. The implication of this research is that the company should encourage the implementation of whistleblowing system as an effective early fraud prevention system, hence the number of fraud will decrease.